Arquitetura para aplicações interativas imersivas de televisão digital - Azevedo, Samuel Oliveira de (2012)
In this work, we propose a new approach to Interactive Digital Television (IDTV), aimed to explore the concepts of immersivity. Several architectures have been proposed to IDTV, but they did not explore coherently questions related to immersion. The goal of this thesis consists in defining formally what is immersion and interactivity for digital TV and how they may be used to improve user experience in this new televisive model. The approach raises questions such as the appropriate choice of equipment to assist in the sense of immersion, which forms of interaction between users can be exploited in the interaction-immersion context, if the environment where an immersive and interactive application is used can influence the user experience, and which new forms of interactivity between users, and interactivity among users and interactive applications can be explored with the use of immersion. As one of the goals of this proposal, we point out new solutions to these issues that require further studies. We intend to formalize the concepts that embrace interactivity in the brazilian system of digital TV. In an initial study, this definition is organized into categories or levels of interactivity. From this point are made analisis and specifications to achieve immersion using DTV. We pretend to make some case studies of immersive interactive applications for digital television in order to validate the proposed architecture. We also approach the use of remote devices anda proposal of middleware architecture that allows its use in conjunction with immersive interactive applications